The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1061/(asce)he.1943-5584.0000924
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Use of Land and Water Resources for Maximizing Farm Income by Mitigating the Hydrological Imbalances

Abstract: DEDICATÓRIAA minha família, especialmente a meus pais, que trabalharam muito para que eu pudesse alcançar mais essa vitória. Dedico também a toda comunidade cientifica e as gerações futuras. Dedico. AGRADECIMENTOSAgradeço primeiramente a Deus por todas as bênçãos e energias positivas que me ajudaram a me manter firme e confiante. Agradeço a Virgem Maria por toda intercessão e todo amor de mãe que me deu e a meu anjo da guarda por toda proteção.Agradeço a meus pais, Atenor César Conceição e Adervane da Silva Lé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…The results of this study are in agreement with the reported results of Owji and Nikkami (2012); Han et al (2016) and Tajbakhsh et al (2018) on the reduction of surface runoff generation through land‐use allocation optimization; and the findings of Sadeghi et al (2009); Nikkami et al (2009); Owji, Nikkami, Mahdian, et al (2012); Sunandar et al (2014); Shaygan et al (2014); Han et al (2016); Lazoglou et al (2016); Sokouti and Nikkami (2017) and Tajbakhsh et al (2018) on the reduction of soil erosion and sediment loads. Moreover, our results are consistent with the reported results of Benli and Kodal (2003); Sadeghi et al (2009); Nikkami et al (2009); Hongrui et al (2010); Owji, Nikkami, Mahdian, et al (2012); Sunandar et al (2014); Yuan et al (2014); Singh (2014); Shaygan et al (2014); Zhou et al, (2015); Mohammadi et al (2015); Lazoglou et al (2016); Sokouti and Nikkami (2017), García et al(2017) and Tajbakhsh et al (2018) on increasing economic returns, and also in agreement with the findings of Shaygan et al (2014) denoting an increase of land use suitability index.…”
Section: Resultssupporting
confidence: 93%
“…The results of this study are in agreement with the reported results of Owji and Nikkami (2012); Han et al (2016) and Tajbakhsh et al (2018) on the reduction of surface runoff generation through land‐use allocation optimization; and the findings of Sadeghi et al (2009); Nikkami et al (2009); Owji, Nikkami, Mahdian, et al (2012); Sunandar et al (2014); Shaygan et al (2014); Han et al (2016); Lazoglou et al (2016); Sokouti and Nikkami (2017) and Tajbakhsh et al (2018) on the reduction of soil erosion and sediment loads. Moreover, our results are consistent with the reported results of Benli and Kodal (2003); Sadeghi et al (2009); Nikkami et al (2009); Hongrui et al (2010); Owji, Nikkami, Mahdian, et al (2012); Sunandar et al (2014); Yuan et al (2014); Singh (2014); Shaygan et al (2014); Zhou et al, (2015); Mohammadi et al (2015); Lazoglou et al (2016); Sokouti and Nikkami (2017), García et al(2017) and Tajbakhsh et al (2018) on increasing economic returns, and also in agreement with the findings of Shaygan et al (2014) denoting an increase of land use suitability index.…”
Section: Resultssupporting
confidence: 93%
“…The burgeoning global population is facing the critical challenge of water shortage for fulfilling its growing domestic, industrial and agricultural demands. The issue will be more serious in coming decades as the per capita availability of fresh water is projected to contract to 50% of its present level in 2025 (Singh, 2014c(Singh, , 2014d. The conjunctive use (COU) of diverse water sources can solve the water shortage issue to some degree by developing water use efficiency (Cheng et al, 2009;Liu et al, 2013;Singh, 2016d).…”
Section: Conjunctive Water Usementioning
confidence: 99%
“…Because of easy formulation and application, the use of LP-based optimization models is very common in the management of water-resource problems (Bender et al 1984;Suryavanshi and Reddy 1986;Kumar and Pathak 1989;Ahlfeld and Heidari 1994;Vedula and Kumar 1996;Khare et al 2007;Azamathulla et al 2008;Lu et al 2011;Singh 2014e). However, NLP models have not been widely used because of rigorous mathematics involved in its development and the high computation time and memory required.…”
Section: Optimization Modelingmentioning
confidence: 99%